The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11695-014-1530-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Morbidity After Totally Robotic Gastric Bypass in 302 Consecutive Patients

Abstract: R-RYGBP is prone to increased complications in the setting of a high preoperative ASA score and revisional surgery. This should be taken into consideration by clinicians when evaluating R-RYGBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In this study, the 60-day major complication rate (Clavien-Dindo score 3 or 4) and reoperation rate were 12.2% and 10.2%, respectively. Fourteen patients (4.6%) had a postoperative anastomotic leak requiring specific surgical management ( 24 ).…”
Section: Primary Proceduresmentioning
confidence: 99%
“…In this study, the 60-day major complication rate (Clavien-Dindo score 3 or 4) and reoperation rate were 12.2% and 10.2%, respectively. Fourteen patients (4.6%) had a postoperative anastomotic leak requiring specific surgical management ( 24 ).…”
Section: Primary Proceduresmentioning
confidence: 99%
“…Arguably, the risk spreads towards continuing professional development too, as it is recognised that educational programmes for the wider surgical robotics teams are urgently needed and that most conferences and courses in this fast-changing area are only available for surgeons (Raheem et al 2017). Finally, RAS requires crucial coordination between the operating surgeon and the BA (Fantola et al 2014, Thiel et al 2013) and the appropriate training of the latter professionals may be essential to further improve perioperative patients’ outcomes (Sessa et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, a retrospective analysis of over 300 patients demonstrated low preoperative hematocrit was found to be a risk factor for 60-day postoperative major morbidity after robotassisted RYGB. 17 Since the release of the annual MBSAQIP PUF, hematocrit has scarcely been acknowledged as a risk factor for 30-day morbidity and mortality in the various contexts of studies which have thus far been reported. It was this important gap in knowledge that provided the impetus to investigate whether preoperative anemia influences short-term morbidity and mortality after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%